A brain origin for factitious disorder (Munchausen's) with malingering? A single case with an old frontal lobe lesion. Issue 1 (2nd January 2021) - Coebergh, Jan Adriaan; Amlani, Aliza; Edwards, Mark; Mah, Yee-Haur; Agrawal, Niruj
ABSTRACT: We describe a patient who presented with gender identity dysphoria and stroke-like symptoms who we diagnosed with Munchausen's syndrome (factitious disorder). We discuss whether a brain lesion in the left frontal cortex is a possible risk factor, and support this hypothesis through neuropsychological investigation, EEG abnormalities, and a personality assessment. This case report supports previous suggestions that underlying brain disease/lesions might be risk factors for Munchausen's syndrome (factitious disorder).